Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.2166/wst.2018.041
|View full text |Cite
|
Sign up to set email alerts
|

Biosorption of cationic dyes by Pará chestnut husk (Bertholletia excelsa)

Abstract: Pará chestnut husk (Bertholletia excelsa) (PCH), an agro-industrial waste largely generated in Brazil, was employed as a low-cost and efficient biosorbent to remove the cationic dyes Crystal Violet (CV) and Methylene Blue (MB) from aqueous media. PCH presented an amorphous structure containing carboxylic acids, esters, ketones and aldehydes on the surface. Non-porous and irregular particles were also observed. For both dyes, the biosorption capacity was favored under acid conditions. Equilibrium was attained w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(19 citation statements)
references
References 13 publications
0
12
0
7
Order By: Relevance
“…Сьогодні багато дослідників займаються розробкою альтернативних до активованого вугілля адсорбуючих матеріалів, охоплюючи побічні продукти сільського господарства, природні глини та полімери [9][10][11][12], які становлять унікальний клас адсорбентів завдяки їхній пористій структурі, здатності до зв'язування, високої адсорбційної здатності та хорошої механічної, хімічної та термічної стабільності [13].…”
Section: вступunclassified
“…Сьогодні багато дослідників займаються розробкою альтернативних до активованого вугілля адсорбуючих матеріалів, охоплюючи побічні продукти сільського господарства, природні глини та полімери [9][10][11][12], які становлять унікальний клас адсорбентів завдяки їхній пористій структурі, здатності до зв'язування, високої адсорбційної здатності та хорошої механічної, хімічної та термічної стабільності [13].…”
Section: вступunclassified
“…Dentre esses métodos, evidencia-se o processo de adsorção, que consiste na remoção dos contaminantes pela interação com algum material adsorvente, sendo um processo eficaz e de fácil manuseio. Em relação aos adsorventes mais aplicados, há as zeólitas, materiais porosos à base de polímeros e o carvão ativado, sendo este o mais utilizado em virtude da sua elevada área superficial (GONÇALVES et al, 2007;GEORGIN et al, 2018;SILVA et al, 2019).…”
Section: Introductionunclassified
“…Adsorbents utilized for dye removal should be characterized by an excellent adsorption capacity derived fundamentally from the combination of pore structure and surface chemistry (Pang et al 2019). Recent literature survey revealed that various adsorbents have been employed in the treatment of dye-polluted waters includes clay minerals (Kausar et al 2018), zeolites (Sivalingam and Sen 2019), polymer composite (Jayasantha Kumari et al 2017), fly ash (Gao et al 2015) and reduced the cost of adsorption process various biomasses have been suggested as dye adsorbents: rice husks (Franco et al 2015), grape wastes (Vanni et al 2017), ouricuri fibers (Meili et al 2017) and para chestnut husk (Georgin et al 2018).…”
Section: Introductionmentioning
confidence: 99%